Pathogen-Negative Sepsis—An Opportunity for Antimicrobial Stewardship. (9th October 2019) - Lockhart, Gabriel C; Hanin, Jacob; Micek, Scott T; Kollef, Marin H
Abstract: Sepsis is a common reason for empiric antibiotics among hospitalized patients. We found that the median duration of empiric antibiotics (interquartile range) was 6 (4–9) days among 1047 survivivors with pathogen-negative sepsis. These findings suggest that patients with pathogen-negative sepsis could represent an important opportunity for antimicrobial stewardship.